The efficacy of cholecalciferol in the comprehensive treatment of patients with autoimmune diabetes - N.V. Pashkovska; I.O. Tsaryk (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Vitamin D deficiency is a global issue negatively affecting the course of autoimmune diabetes, including classical type 1 diabetes mellitus (T1DM) and latent autoimmune diabetes in adults (LADA). Vitamin D plays a vital role in immune response regulation, maintaining β-cell function of the pancreas, and metabolic balance. The purpose of the study was to evaluate the efficacy of adding cholecalciferol at a dose of 20,000 IU (once weekly for 3 months) to standard therapy to improve the metabolic status of patients with T1DM and LADA. Materials and methods. A total of 72 patients participated in the study: 36 with T1DM and 36 with LADA. They were divided into subgroups depending on the treatment received: basic therapy or basic therapy with vitamin D supplementation. A comprehensive evaluation of carbohydrate metabolism indicators (fasting glycemia, HbA1c, HOMA-IR, insulin, and C-peptide levels), autoimmune activity (antibodies to glutamic acid decarboxylase (antiGAD)), and lipid profile was conducted before and after treatment. Results. The addition of vitamin D to therapy significantly increased serum 25(OH)D levels, ensuring a substantial improvement in metabolic status of patients. In groups receiving supplemental cholecalciferol, there was a notable reduction in fasting glucose levels, HbА1с, HOMA-IR, and antiGAD titers, indicating a positive impact on glycemic control and a decrease in autoimmune activity. Additionally, patients receiving vitamin D exhibited improvements in lipid metabolism, including decreased levels of total cholesterol, low-density lipoprotein cholesterol, triglycerides, and increased levels of high-density lipoprotein cholesterol. Particularly significant was an increase in C-peptide levels observed in patients with LADA, reflecting enhanced β-cell function in the pancreas. This effect may be related to the reduction in autoimmune activity as well as the anti-inflammatory properties of vitamin D, which contribute to the maintenance of β-cells and their ability to secrete insulin. The study confirms the pleiotropic effects of vitamin D: reducing autoimmune inflammation, improving insulin sensitivity, normalizing lipid profiles, and supporting β-cell function. Conclusions. The findings highlight the importance of monitoring and correcting vitamin D levels in patients with T1DM and LADA, particularly in the presence of deficiency. The above data could be used to optimize therapeutic approaches and reduce the risk of complications in this patient population.